PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP PENGUASAAN KOSAKATA (VOCABULARY) PESERTA DIDIK DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN BAHASA INGGRIS KELAS I SD NEGERI 090612 MEDAN TAHUN PEMBELAJARAN 2024/2025 - Banjarnahor, Roslitha Uli; Marah Doly Nasution; Dermawan Nasution (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This Classroom Action Research aims to improve class I students' vocabulary mastery through interactive learning media (Animation) at SD Negeri 060912 Medan for the 2024/2025 academic year. Initial observations showed that students' vocabulary mastery was not in accordance with the expected development. Only 8 out of 21 students were able to recognize English vocabulary well, while most had difficulty recognizing vocabulary because it was rarely found and the memory of class 1 students was still low. Overcoming this problem, research uses interactive learning media to improve the ability to master vocabulary. There were 21 students (12 men and 9 women) as subjects. The research instruments included observation sheets, LKPD, and pretest and posttest cycles 1 and 2. The research results showed a significant increase in vocabulary mastery: in cycle I, 38.95%) of students had not reached the Criteria for Achievement of Learning Goals (KKTP), while in cycle II, 81.00% of students have exceeded the KKTP. This shows that the use of interactive learning media is effective in increasing students' vocabulary mastery.